2008
DOI: 10.1073/pnas.0711319105
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and liquid crystallization of complementary sequences in mixtures of nanoDNA oligomers

Abstract: Using optical microscopy, we have studied the phase behavior of mixtures of 12-to 22-bp-long nanoDNA oligomers. The mixtures are chosen such that only a fraction of the sample is composed of mutually complementary sequences, and hence the solutions are effectively mixtures of single-stranded and double-stranded (duplex) oligomers. When the concentrations are large enough, such mixtures phase-separate via the nucleation of duplex-rich liquid crystalline domains from an isotropic background rich in single strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 31 publications
9
84
0
Order By: Relevance
“…Scientists employing different techniques, like x-ray crystallography, 1 dynamic light scattering, 2 or from different areas like spectroscopy and separation science 3 have dealt with optical active aggregates of chiral molecules in the solid state. Yet the main techniques are optical rotatory dispersion and circular dichroism (CD), and scientists listed above are aware of this and ask for help and collaboration from experts in the field: this is what has motivated us in writing this review.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists employing different techniques, like x-ray crystallography, 1 dynamic light scattering, 2 or from different areas like spectroscopy and separation science 3 have dealt with optical active aggregates of chiral molecules in the solid state. Yet the main techniques are optical rotatory dispersion and circular dichroism (CD), and scientists listed above are aware of this and ask for help and collaboration from experts in the field: this is what has motivated us in writing this review.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations have revealed that the process of LC formation is selective, such that in an all-or-nothing mixture of complementary and noncomplementary oligomers the complementary oligomers tend to be incorporated into the LC domains and segregated from the surrounding isotropic phase of noncomplementary strands (9). Altogether, these findings, obtained with controlled sequences and involving at most mixtures of a few of them, reveal a remarkable and finely tuned combination of staged self-assembly: DNA hybridization, linear aggregation, liquid crystallization, phase separation, and condensation of sequences.…”
Section: Lc Ordering Of Complementary Dna Sequencesmentioning
confidence: 99%
“…The selectivity of DNA binding can also be exploited to control the mutual interactions between the structures (14,15), whereas the spontaneous assembly of DNA sequences enables producing large ensembles of particles. These properties make DNA a powerful tool to explore fundamental phenomena of soft matter and statistical physics, as indicated by previous studies of liquid-crystalline ordering and phase separations in solutions of short DNA oligomers (16)(17)(18)). Here we exploit DNA self-assembly to experimentally address the phase behavior of particles interacting with specific valence, strength, and selectivity.…”
mentioning
confidence: 99%